Pengaruh Perceived Ease of Use, Perceived Security, dan Perceived Reputation Terhadap Kepercayaan Awal Pemberi Pinjaman Pada Platform P2P Lending - Islamiah, Diniyatul; Ningtyas, Mega Noerman (Jurnal Ecogen, 2024)
This research objectives to examine the influence of perceived ease of use, perceived security, and perceived reputation on the initial trust of lenders on P2P lending platforms. The population under study consists of all Generation Z individuals residing in the city of Malang who have previously invested in P2P lending platforms. A sample of 180 respondents was selected through purposive sampling, with criteria including residency in Malang, aged between 17-26 years old, and having previous or current investment experience in P2P lending platforms. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The findings of the research reveal that perceived ease of use, perceived security, and perceived reputation significantly influence initial trust.